Some peculiarities of students’ perception and observation in botany lessons - Kulvičienė, A. (Psichologija, 1963)
The article discusses some peculiarities of perception and observation of students of 6th-8th grades in botany lessons. In students’ assimilation of botany knowledge, a big role is played by perception and observation of perceptible features. The aim of the investigation is to find out how students create abstractions during direct perception (whether they are able to distinguish the most important parts, identify their similarities and differences during observation of plant views). The results of investigation have shown that a significant part of 6th-7th grades students distinguish not all essential parts of plants but only some of them in the observed views. Others wrote “forgot” in their answers. This shows that they either did not put any effort to observe the demonstrated views and distinguish their essential elements and relied solidly on previously acquired knowledge or were not able to do the analysis. It was even more difficult for students to establish the similarities and differences. The more active thinking was required, the more mistakes the students made. All this allows us making conclusion that the observation process of the students of 6th-7th grades has to develop further as active cognitive activity.